Antibiotic and Antimicrobial Metal Resistance in Escherichia coli from Livestock - Zhou, Weijie (2025)
Antibiotic resistance is a global threat, with misuse and overuse of antibiotics as key drivers. Metal exposure has also been hypothesized to promote bacterial resistance through co-selection mechanisms. This study comprehensively investigated the impact of metal exposure on multidrug resistance using Escherichia coli isolates from livestock and wastewater. Zinc supplementation in animal feed significantly increased zinc tolerance in E. coli isolates but no correlation between zinc treatment and multi-drug resistance prevalence was observed in a large-scale analysis of isolates from a pig feed trial. Notably, wastewater E. coli isolates exhibited a unique zinc resistance phenotype, inducible by low zinc concentrations and reversible upon zinc removal. Whole-genome sequencing of mercury resistant E. coli isolates from pig feed trials identified a novel Tn21-like transposon carrying nine resistance genes, revealing the genetic diversity and integrative potential of the Tn21 family. Additionally, the Copper Homeostasis and Silver Resistance Island (CHaSRI) mobile genetic elements were also identified from pig feed trials provided new insights into the horizontal transfer of metal resistance genes, emphasizing the impact of high local accumulations of metal ions on environmental microorganisms, animals, and humans.